Análise de contaminações microbiológicas e otimização de parâmetros de processo de produção do Nonilfenol 9,5 EO Sulfato de Sódio - Girodo, Luis Felipe de Morais (Universidade Federal de São Carlos, 2025)
This study aims to identify and analyze critical points in the production process of the surfactant Nonylphenol 9,5 EO Sodium Sulfate that favor the occurrence of microbiological contamination, with the goal of proposing operational improvements to guarantee the final product quality. The methodology adopted consisted of a retrospective comparative analysis of industrial data collected over a 17-month period, between 2024 and 2025, comparing in detail five productions that presented microbiological deviations with five productions free of contamination. The investigation revealed that the vulnerability of the system does not derive from an isolated factor, but rather from the interaction between operational instability and inefficiency in the correction and homogenization steps. The results demonstrated that the contaminated batches presented significant variations in critical parameters such as pH, color, and insulfate content, indicating failures in the efficiency of the sulfonation and sulfation reactions. It was observed that this process instability requires multiple interventions for adjustments, which prolongs the processing time and delays the addition of the preservative (formaldehyde). This delay creates vulnerability, where the product remains exposed and susceptible to microbial proliferation before complete stabilization. In conclusion, the study proposes changing the order of adjustments made to the product, as well as anticipating the start of recirculation to ensure homogeneity simultaneous to production, and suggests the implementation of a record-keeping system dedicated exclusively to the adjustment steps, essential measures to reduce process variability and ensure compliance.
Analysis of microbiological contamination and optimization of process parameters for the production of Sodium Nonylphenol 9.5 EO Sulfate
Keywords: Sulfonação; Sulfatação; Controle microbiológico; Surfactantes aniônicos; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura